Modern Approaches To Surgical Treatment Of Congenital Malformations Of The Gastrointestinal Tract In Newborns - Gazizova, Kamila Kamilievna; Plekhanova, Svetlana Vladislavovna; Nizhutina, Kristina Valeryevna; Belkovich, Natalya Andreevna; Bembeeva, Aisa Olegovna; Daudova, Zaira Dzhambulatovna; Petrenko, Elena G. (Journal of Neonatal Surgery, 2025)
The presented scientific work presents the results of a comprehensive study of modern methods of surgical treatment of congenital malformations of the gastrointestinal tract in newborns. The study was retrospective and prospective in nature and covered 124 patients with various forms of congenital anomalies of the oesophagus, stomach, duodenum, small and large intestine. Special attention was paid to the comparative analysis of minimally invasive technologies and traditional cavity surgeries. Survival rates, recovery time, nature of complications and long-term results of surgical intervention were studied. Preoperative preparation was carried out in compliance with the principles of neonatal resuscitation and with the use of modern diagnostic techniques. It was shown that the use of laparoscopic and thoracoscopic techniques under certain conditions contributes to a significant reduction in mortality and the incidence of infectious complications. It has been established that the reduction of the duration of stay of a newborn baby in the intensive care unit is directly related to less traumatic minimally invasive interventions. The importance of multidisciplinary approach including surgeons, neonatologists, anaesthesiologists-resuscitators and other specialists was emphasized, which allows to increase the effectiveness of treatment. Generalization of the results obtained gives grounds to assert that further introduction and improvement of minimally invasive methods can significantly increase the effectiveness of treatment. Generalization of the obtained results gives grounds to assert that further introduction and improvement of minimally invasive methods can significantly increase the efficiency of surgical treatment of congenital malformations of the gastrointestinal tract in newborns.